Agomelatine Efficacy in the Night Eating Syndrome. (16th May 2013) - Milano, Walter; De Rosa, Michele; Milano, Luca; Capasso, Anna
Abstract : Night eating syndrome (NES) is a nosographic entity included among the forms not otherwise specified (EDNOS) in eating disorders (ED) of the DSM IV. It is characterized by a reduced food intake during the day, evening hyperphagia, and nocturnal awakenings associated with conscious episodes of compulsive ingestion of food. Frequently, NES patients show significant psychopathology comorbidity with affective disorders. This paper describes a case report of an NES patient treated with agomelatine, an antidepressant analogue of melatonin, which acts by improving not only the mood but also by regulating sleep cycles and appetite. After three months of observation, the use of Agomelatine not only improved the mood of our NES patient (assessed in the HAM-D scores) but it was also able to reduce the night eating questionnaire, by both reducing the number of nocturnal awakenings with food intake, the time of snoring, the minutes of movement during night sleep (assessed at polysomnography), and the weight (−5.5 kg) and optimizing blood glucose and lipid profile. In our clinical case report, agomelatine was able both to reduce the NES symptoms and to significantly improve the mood of our NES patient without adverse side effects during the duration of treatment. Therefore, our case report supports the rationale for further studies on the use of Agomelatine in the NES treatment.